Literatura y estudios literarios - Vaisman, Luis (Revista Chilena de Humanidades, 2015)
The author presents the problem of the understanding of the meaning of literature in relation with the environment, contents, quelity and function, saying that it is easier to achieve this if we consider it as an activity proper to a time and a certain locality. Through a consideration of various scholars in different periods of time, he says that poetics, grammar and rhetoric ·limit the notion of literature, giving origin to criticism, which leads to the history of authors and of their works; consequently, literary investigations have been carried out up to now in three directions, theory, criticism and history, without leaving out the process of teaching. Diverse positions of the science of literature and the evidence of the decay of realism, show the predominance of the literary as anesthetic pleasme, "based more on the wanting to do than on the wanting to say."